PENENTUAN PUSAT PERTUMBUHAN SEBAGAI ARAHAN PENGEMBANGAN KAWASAN PERDESAAN DI KECAMATAN CIJERUK KABUPATEN BOGOR - Mega Fernandina; Mujio Mujio; Yeriko Septiawan; Janthy Trilusianthy Hidayat; Dion Achmad Armadi; Novida Waskita Ningsih; Habil Nugraha; Rindiani Agustina Rahayu; Devi Komala Sari (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2023)
Regional disparities are caused by the different development approaches taken in rural and urban areas that must be integrated. The development of rural areas must be followed by the development of inter-village growth centers that connect rural areas with urban areas in an integrated manner. This study aimed to determine the growth centers of rural areas that function as production, processing, marketing, training, and government service centers in rural regions of Cijeruk District. Four aspects determine the center of growth in rural areas: the infrastructure aspect, the social aspect, the physical aspect, and the economic aspect. This research uses scalogram analysis, Hansen analysis, disaster risk analysis, population analysis, and the analytical hierarchy process. The results of the research point to Cijeruk Village as a growth center for rural areas in the Rural Cijeruk District because it is supported by four variables with large values, for instance, public facilities, growth rate, population density, and regional attractiveness.